2019
DOI: 10.1038/s41419-019-2083-2
|View full text |Cite
|
Sign up to set email alerts
|

MKK3 sustains cell proliferation and survival through p38DELTA MAPK activation in colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors worldwide and understanding its underlying molecular mechanisms is crucial for the development of therapeutic strategies. The mitogen-activated protein kinase-kinase 3 (MKK3) is a specific activator of p38 MAP kinases (p38 MAPKs), which contributes to the regulation of several cellular functions, such as proliferation, differentiation, apoptosis as well as response to drugs. At present, the exact MKK3/p38 MAPK pathway contribution in cancer is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…We recently demonstrated that p38δ MAPK, mainly activated by upstream MKK3 kinase in CRC, is further activated by 5-FU, thus hampering its efficacy. The p38δ MAPK inhibition by RNAi improves 5-FU response in CRC lines in vitro and in vivo [18]. Of interest with identical experimental CRC models, the pharmacologic p38α MAPK inhibition (SB203580) exerts protective effects against 5-FU induced apoptosis, suggesting that, in addition to an MKK3/p38δ MAPK pro-survival signaling, a p38α MAPK pro-apoptotic signaling is triggered by 5-FU and possibly mediated by a different upstream kinase (likely, MKK6) [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently demonstrated that p38δ MAPK, mainly activated by upstream MKK3 kinase in CRC, is further activated by 5-FU, thus hampering its efficacy. The p38δ MAPK inhibition by RNAi improves 5-FU response in CRC lines in vitro and in vivo [18]. Of interest with identical experimental CRC models, the pharmacologic p38α MAPK inhibition (SB203580) exerts protective effects against 5-FU induced apoptosis, suggesting that, in addition to an MKK3/p38δ MAPK pro-survival signaling, a p38α MAPK pro-apoptotic signaling is triggered by 5-FU and possibly mediated by a different upstream kinase (likely, MKK6) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, genetic depletion of the p38α MAPK isoform (main target of the SB203580) also exerted protective effects against 5-FU induced apoptosis, confirming that p38α MAPK isoform activation mediates pro-apoptotic signaling in response to this chemotherapeutic agent [12], and hence, arguing against the use of p38 MAPK inhibitors as perspective therapeutic agents to be exploited in combination with chemotherapy [23]. More recently, it was demonstrated that, in response to 5-FU exposure, CRC cells display activation of the p38δ MAPK isoform and that depletion of either p38δ MAPK or its upstream kinase MKK3 (MAP2K3) univocally exerts antitumor effects [18]. This observation highlights the importance of isoform-specific activation of the p38 MAPK in mediating different effects and, in fact, provides a possible explanation for the contradictive effects reported for p38 MAPK activation in response to 5-FU.…”
Section: -Fluorouracil Effects On the P38 Mapk Signaling Pathway In Crcmentioning
confidence: 97%
See 1 more Smart Citation
“…To gain insights into mechanism of TRIM67 as a CRC suppressor, RNA sequencing in present study revealed that TRIM67 targeted MAPK11 to play a tumor suppressor role in CRC cells. Studies have showed that MAPK signaling pathways are involved in tumor progression, cell growth, cell proliferation, and metastasis in CRC [19][20][21][22]. The MAPK pathways include extracellularregulated kinases 1 and 2 (ERK1/ERK2), c-Jun N-terminal kinases (JNKs), p38 (MAPK11-14), and extracellular-regulated kinase 5 (ERK5).…”
Section: Discussionmentioning
confidence: 99%
“…The role of MAP2K3 in cancer progression is contradictory. MAP2K3 has been shown to enhance tumor progression, and the loss of MAP2K3 results in inhibition of cellular proliferation and increased response of tumor cells to chemotherapeutic drugs in vivo [5,12,13]. However, recent research has demonstrated that the loss of MAP2K3 copy number occurs in NSCLC and that MAP2K3 inhibits cell proliferation and promotes cellular senescence in hepatocellular carcinoma, breast cancer and melanoma [7,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%